Collaborative method consisting lecture, problem-based learning and weblog for clinical courses of medical students in comparison with lecture method - Masoumeh Sharifzadeh; Jila Agah; Ahmad Khosravi; Shahram Samadi; Seyd Javad Davari Sani (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Lecture is a common teaching method, which is not considered efficient for the development of critical and intellectual acquisition in the students of clinical courses. Although in theory combined methods are known acceptable, in practice, they are not commonly applicable. The present study aimed to compare the combination of problem-based learning (PBL), weblogs, and lectures with lecture alone to achieve an advantageous teaching method for clinical courses. MATERIALS AND METHODS: This quasi-experimental study was conducted on 63 medical students (5th year) taking obstetrics and gynecology clinical courses at Sabzevar University of medical sciences, Iran. The participants were selected via census sampling. Based on the Student's number and using the random number table, the students were randomly assigned to two groups of interventions. The exclusion criteria were unwillingness to participate and absence for more than two sessions. Initially, the similarity of obstetrics and gynecology knowledge in both groups was confirmed based on a pretest (P > 0.05). A conventional lecture was performed for both groups. In the intervention group (B), the researcher asked each student (32 persons) to provide a case/problem from mentioned subjects outside the class concerning the given lecture and upload it to the lecturer's weblog to show commonalty. In the next session, the presented cases were initially discussed, and another lecture was carried out. Finally, two methods were compared through identical theoretical and practical exams and scored based on a Likert scale using a questionnaire. Data analysis was performed in SPSS 19 using t-test and Chi-square at the significance level of P < 0.05. Results: Group B achieved higher grades in the scientific exams (P < 0.001), especially in the domains of perception, learning and memorizing of subjects, motivation, and communication with the classmates and tutor (P = 010). Therefore, satisfaction was higher in the intervention group compared to the control group (P = 0.001). Conclusion: The training of pensive, creative, and active experts for the future of medicine requires the combination of new collaborative methods with lectures, which are undoubtedly effective learning techniques. According to the results, PBL and weblogs could be invaluable for the improvement of students' knowledge, as well as the relations between tutors and students.